Land use changes in Mariborske gorice in the period 2000-2014, in relation to selected physical geographical indicators - Žiberna, Igor (Journal for Geography, 2014)
Article analyzes land use changes in the area of Mariborske gorice, between 2000 and 2014. Eleven land categories were studied. Land use changes for the given categories were further analyzed in comparison with an altitude, relative heights, slopes, aspect, global irradiation, soil types and lithological structure. Changes of the vineyard areas were analyzed separately in relation to the vineyard profit (preferable topoclimatic positions) and in relation to their exploitation. Analysis revealed that the extensification and the untapping of first-class vineyard lands were the most pronounced processes in the studied period.